P243 Outcome measures for airway clearance in adults with cystic fibrosis (CF): a randomised controlled crossover trial. (12th November 2019) - Stanford, GE; Cathcart, F; Beverley, Z; Short, C; Jones, M; Bilton, D; Davies, JC; Simmonds, NJ
Abstract : Introduction: The best outcome measure (OM) for airway clearance (AC) in CF is unknown. Our National Institute for Health Research funded RCT compares standard OMs (sputum weight, FEV1 ) to new OMs (electronic impedance tomography (EIT), lung clearance index (LCI), impulse oscillometry (IOS)) to determine the most effective measure of AC. Here we describe our ongoing AC trial, present the challenges related to recruitment, baseline characteristics and OM reproducibility. Methods: Subjects complete the OMs of LCI, IOS and FEV1 then are randomised to either supervised AC intervention or rest for 30 minutes. LCI, IOS and FEV1 are repeated straight afterwards. EIT, oxygen saturations and sputum are collected during the rest/AC period. At a subsequent visit the OMs are completed with the other intervention. Sequence allocation is blinded to the research team. Difference in change in the OMs pre- and post- AC/rest is the primary endpoint. Target sample is 96, the sample was calculated with 80% power and significance of 5% for each OM. Results: Recruitment to date (after 19 months): 241 patients pre-screened, 12 await first visit, 6 enrolled, 31 completed (66% of target to date (TTD)). Completed subjects' demographics: 19 male; median age 38yrs (IQR 19.5); 45% F508del/F508del; median FEV1 70%pred (IQR 29.5). Scheduled visits are at 155% of TTD, but completed visits are at 76% of TTD. The high cancellation rate is primarily caused by patient illness. Median visit length 205 minutes (IQR 47). LCI has the longest duration; ICCs of pre-intervention OMs are good between visits (table). Conclusion: Completion of study visits is challenging, especially due to inclusion/exclusion criteria and requiring patient stability. Recruitment has improved recently with enhanced communication and strategic overbooking. The newer OMs of LCI, IOS and EIT are reproducible and feasible; however, the long duration of LCI may inhibit future use in this cohort. We believe this RCT is the first to evaluate these OMs for use in CF AC trials. The need to identify a more robust OM for AC effect remains paramount for future scientific research and for the application of personalized therapy not only for CF but for other supperative chest diseases.